Production And Risk Affecting Factors of Soybean Farming in Banyumas Regency Central Java Province, Indonesia - Kartika Eka Wijayanti Irene; Darmawati Putri Dindy; Kusnaman Djeimy; Al Ghifari M. F.; Yuliyana A. S.; Mulyani Altri; Adhi Saputro Wahyu (E3S Web of Conferences)
Indonesia’s soybean consumption is rising in tandem with population growth, but it is not keeping pace with output. Farmers need to be encouraged to continue planting soybeans. The purpose of this study is to establish the function of soybean production, including production hazards and affecting factors in Banyumas Regency. The study was conducted in Banyumas Regency in August and October of 2023. Using simple random selection, 200 farmers who planted soybeans in 2022 were chosen from a population of about 2000 farmers. The Ordinary Least Squares (OLS) approach in conjunction with the Cobb-Douglas function was the data analysis tool used to identify significant variables influencing soybean production. The level of risk connected to soybean yield was determined using the coefficient of variation. Finally, Just and Pope’s production risk function model was utilized to identify the components influencing the risk of soybean production. The findings showed that labor, land area, fertilizers, seeds, and insecticides all significantly affect soybean production. There is a high level of production risk associated with soybean farming in Banyumas Regency, with a coefficient variation of 0.54 (≥0.5); and labor has no significant effect on soybean production risk, while land area, fertilizers, seeds, and insecticides do.